Commun salt application as a treatment for percutaneous endoscopic gastrostomy periostomal granuloma - Frías-Ordoñez, Juan Sebastián (2024)
Percutaneous endoscopic gastrostomy (PEG) is an important procedure for nutrition delivery, and one that is often associated with complications. The formation of granulation tissue or periostomal granuloma is a chronic minor complication associated with gastrostomy, being more frequent in geriatric patients, but the therapeutic experience in pediatric patients is better known. We present the case of a 94-year-old female patient, diagnosed with Alzheimer's dementia with severe motor and cognitive impairment, who presents significant malnutrition and severe dysphagia. In treatment with rivastigmine, sertraline, and trazodone, in addition to muscle relaxant. She has been a gastrostomy user for 2 years due to severe motor and swallowing compromise. In the past 1 year ago with presence of ring granuloma, without bleeding. It was decided to treat with common salt as the first line of treatment since there was no bleeding. The primary caregiver was instructed on the details of how to apply common salt on the granuloma at home. The patient showed complete resolution of the granuloma within three days of application with no recurrence at follow-up 12 months after the initial evaluation, and without requiring a tube change. PEG-associated granuloma is a frequent minor chronic complication in adult gastrostomy users. The use of common salt is an effective, rapid and safe therapeutic alternative to consider in these patients.